On the theory of the initial stage of slow nuclear burning - Khizhnyak, N. (Вопросы атомной науки и техники, 2001)
Scientific principles of linear nuclear power systems of slow burning are elaborated. Two concepts of a slow burning reactor, one using U-Pu cycle and the other Th-U cycle are proposed. In the first concept the reactor is approximated by a homogeneous media and operates with fast neutrons. In the second concept the reactor is a heterogeneous assembly using both fast and thermal neutrons. The fast neutron flux at the initial stage after the reactor was ignited was determined for both concepts.